2012
DOI: 10.2190/ic.32.1.g
|View full text |Cite
|
Sign up to set email alerts
|

Book Review: Imagine That: Studies in Imagined Interaction

Abstract: Everyone experiences Imagined Interactions (II). They are universal and time immemorial. In fact, the tendency to engage in IIs is so natural that its process often eludes us! Honeycutt and his colleagues have ambitiously plunged into our inner worlds with scientific lenses. They have discerned the importance of IIs 95

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As demonstrated by previous studies, IIs can benefit those in the workplace as they recall conversations with supervisors and colleagues as well as prepare for presentations and important interactions (Choi et al, 2015). Additional studies (Croghan & Croghan, 2010;Croghan & Kelley, 2004) have found significant correlations in individuals' workplace experiences and their experiences with IIs. For example, in a 2010 study, Croghan and Kelley found that work experience and the discrepancy of IIs are negatively correlated, with those who have more work experience reporting less discrepant IIs.…”
Section: Levels Of Camentioning
confidence: 80%
See 1 more Smart Citation
“…As demonstrated by previous studies, IIs can benefit those in the workplace as they recall conversations with supervisors and colleagues as well as prepare for presentations and important interactions (Choi et al, 2015). Additional studies (Croghan & Croghan, 2010;Croghan & Kelley, 2004) have found significant correlations in individuals' workplace experiences and their experiences with IIs. For example, in a 2010 study, Croghan and Kelley found that work experience and the discrepancy of IIs are negatively correlated, with those who have more work experience reporting less discrepant IIs.…”
Section: Levels Of Camentioning
confidence: 80%
“…For example, in a 2010 study, Croghan and Kelley found that work experience and the discrepancy of IIs are negatively correlated, with those who have more work experience reporting less discrepant IIs. Croghan and Croghan (2010) identified ways in which IIs can improve workplace communication, including helping prospective employees prepare for job interviews, helping to plan what one will say before a meeting, and utilizing the catharsis and rehearsal functions of IIs to avoid conflict at meetings.…”
Section: Levels Of Camentioning
confidence: 99%